Estudio para la implementación de un microaerogenerador en la finca La Bella en zona rural del municipio de Acevedo Huila. (2021)
The world experiences a great need for electrical energy and alternative energies represent a solution, Law 1715 of 2014 in Colombia promotes new renewable energy projects, the present study was conducted to provide an alternative solution. The project was divided into the phases “Estudio previo”, “Estudio intensivo” and two stages “Mes 1” and “Mes 2”, a total of 95.760 were collected and analyzed using the frequency distribution, Weibull and WAsP, the Annual Average Wind Speed was 5,7 and 6,5 / and wind power density of 135,2 and 186,2 W m2 ⁄ respectively for each stage.